Protective effect of Monarda didymaL. essential oil and its main component thymol on learning and memory impairment in aging mice - Guo, Yingxue; Qu, Yan; Li, Wenpeng; Shen, Hongkuan; Cui, Jiwen; Liu, Jiguang; Li, Jinlian; Wu, Dongmei (Frontiers in Pharmacology, 2022)
The aging process of human beings is accompanied by the decline of learning and memory ability and progressive decline of brain function, which induces Alzheimer's Disease (AD) in serious cases and seriously affects the quality of patient’s life. In recent years, more and more studies have found that natural plant antioxidants can help to improve the learning and memory impairment, reduce oxidative stress injury and aging lesions in tissues. This study aimed to investigate the effect of Monarda didymaL. essential oil and its main component thymol on learning and memory impairment in D-galactose-induced aging mice and its molecular mechanism. The composition of Monarda didymaL. essential oil was analyzed by GC-MS. A mouse aging model was established by the subcutaneous injection of D-galactose in mice. The behavior changes of the mice were observed by feeding the model mice with essential oil, thymol and donepezil, and the histopathological changes of the hippocampus were observed by HE staining. And the changes of AchE, SOD and GSH-Px activities, and the content of MDA in hippocampal tissues were detected by corresponding kits. And detecting the expression of MAPK and Nrf2/HO-1 pathways related proteins. The protein expressions were detected by western blot. Animal experimental results showed that compared with model group, the above indexes in Monarda didymaL. essential oil and thymol groups were significantly improved in a dose-dependent manner. Monarda didymaL. essential oil and its main active component thymol can improve the learning and memory impairment of aging mice to some extent, and Nrf2/HO-1 and MAPK pathways may be involved in its action process.